If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a * 9a = 0 Reorder the terms for easier multiplication: 4 * 9a * a = 0 Multiply 4 * 9 36a * a = 0 Multiply a * a 36a2 = 0 Solving 36a2 = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '36'. a2 = 0 Simplifying a2 = 0 Take the square root of each side: a = {0}
| 96=2(6+2x)+2(x) | | (-12)+(-23)= | | (x^2+13)=225 | | 10=x+8 | | 32-12t+t^2= | | 21x^2+11x-6=0 | | 2*(x+5)=37 | | 3x-2=x+8 | | 14x=-17 | | x-7+x=3x+4 | | 1-2x+4x=8 | | 2(0)+5y=0 | | x+(-14)=5 | | y-7xy=3y+4 | | 11+4x=7x-13 | | 2x+5(0)=0 | | 6x+123=16x-7 | | 3b-5=16 | | (2-3x)*5-4(8-x)=0 | | 15x^2-91x+6= | | -5x+3(0)=6 | | 8-8x=34-22x | | -35-8x=10x+19 | | 19764845-7564524+5424-214241=11991504 | | 3+3y=3-(5y+2) | | 6x+7=71-2x | | 19764845-7564524+5424-214241=33 | | 152-4x=6x+22 | | 3x+9=7x-11 | | 5x+6-x=-7+x-2 | | 4x-6=x+3 | | 2x(3x-4)=3x(2x+1)-11 |